Estudio comparado y socio jurídico de la unión de hecho desde el caso ecuatoriano con los países de América Latina y/o la Unión Europea - Argüello Terán, María Elena (2018)
The purpose of this study is to make a socio-legal comparison of the de fact union from the Ecuadorian case with the countries of Latin America and / or the European Union, Ecuador-Estonia case. The unions in fact, have generated vertiginous changes in society based on different criteria that have been presented worldwide. All this has led to the reform of laws and especially the inclusion of these couples in today's society. We must consider a specific point; the various forms of unions in fact have generated fundamental changes in current families, so we must consider that family unity and coexistence are fundamental in the current changes. The family is and will be the fundamental pillar that should never change in society. The present work has the purpose of verifying data related to said unions, through the application of qualitative and quantitative processes. One of the techniques applied in this research work was the survey, which was conducted to twenty legal professionals, professionals it was developed and analyzed according to different criteria based on current knowledge about de fact union.